Fulminant hepatorenal syndrome due to Acetaminophen toxicity: A case report - Nekoukar, Zahra; Moghimi, Minoo; Zakariaei, Zakaria; Fakhar, Mahdi; Tabaripour, Rabeeh (Clinical case reports, 2021)
HRS is a rare and poor prognosis complication of chronic acetaminophen toxicity, which presents by progressive decline in renal function secondary to liver failure. HRS is a rare and poor prognosis complication of chronic acetaminophen toxicity, which presents by progressive decline in renal function secondary to liver failure.